2012
DOI: 10.1039/c2nr30090g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of silver/alanine nanocomposites for radiation detection in medical applications: the influence of particle size on the detection properties

Abstract: Silver/alanine nanocomposites with varying mass percentage of silver have been produced. The size of the silver nanoparticles seems to drive the formation of the nanocomposite, yielding a homogeneous dispersion of the silver nanoparticles in the alanine matrix or flocs of silver nanoparticles segregated from the alanine crystals. The alanine crystalline orientation is modified according to the particle size of the silver nanoparticles. Concerning a mass percentage of silver below 0.1%, the nanocomposites are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 63 publications
4
50
0
2
Order By: Relevance
“…In other words, the size of the gold nanoparticles in the composites bearing gold, does not vary (~5 nm), whereas the size of silver nanoparticles in the silver/alanine composites rises with increasing silver content. Furthermore, TEM images revealed that large silver particles become segregated from the alanine matrix 9,42 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In other words, the size of the gold nanoparticles in the composites bearing gold, does not vary (~5 nm), whereas the size of silver nanoparticles in the silver/alanine composites rises with increasing silver content. Furthermore, TEM images revealed that large silver particles become segregated from the alanine matrix 9,42 .…”
Section: Resultsmentioning
confidence: 99%
“…3) 41 . For the case of silver nanocomposites, the DEF as calculated by ESR dosimetry was shown to be sensitive to nanoparticle concentration, size, and position in the alanine composites 9,41 . In this case, optimum DEF occurs for silver nanoparticles smaller than 30 nm homogeneously distributed in the sensitive medium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations